Review essay: how rational is international law? - Niels Petersen (Max Planck Institute for Research on Collective Goods, 2009)
Economic approaches are becoming increasingly prominent in international law. A few years ago, Jack Goldsmith and Eric Posner caused a great stir with their account of The Limits of International Law, in which they argued that international law did not have any effect on state conduct. This contribution reviews two recent books analyzing the effectiveness of international law from an economic perspective. Both authors, Andrew Guzman and Joel Trachtman, take a much more differentiated approach than did Goldsmith and Posner, thus making analytical methods of economics more acceptable for mainstream international law scholarship. Still, this contribution argues that we should be cautious to perceive the economic perspective as a holistic explanation of how international law works. Economic models are, for methodological reasons, based on certain assumptions. The analytical tools are thus only capable to answer a certain range of questions so that they have to be complemented by other theoretical approaches. Therefore, we have to be very cautious with policy recommendations that are based on a purely economical perspective.
Keywords: 330; Internationales Recht; Rechtsökonomik